1972
DOI: 10.1109/tns.1972.4326804
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray-Induced Photoconductivity in Dielectric Films

Abstract: LAWRENCE UVERMORE LABORATORY MS, tlaio; April 27, U"T2 -NOTICE-This, report n prepared as an accotrat of work spaasored fay the United States Gofcrnment. Neither tt~ United States nor the United States Atomic Energy CaamiB»n, nor any of t^-cir employees, nor any of thek contractors, fecoatneton. or their cmpSoyees. makes any warrant, express or implied, or essoincs any legal EacOity or responsibility for the teem icy. com* pUteness or cieiqtoess of any inforcutioa, sppvitos, product or process diseased, cr rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In situ and ex situ transmission X-ray experiments at low temperatures commonly use Kapton HN-type polyimide capillaries as sample holders because of their optical properties (Arakawa, 1981), X-ray photoconductivity (Weingart et al, 1972;Pillai & Sharma, 1979), resilience and low cost (Chupas et al, 2008). This poly(oxydiphenylene-pyromellitimide) polyimide ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In situ and ex situ transmission X-ray experiments at low temperatures commonly use Kapton HN-type polyimide capillaries as sample holders because of their optical properties (Arakawa, 1981), X-ray photoconductivity (Weingart et al, 1972;Pillai & Sharma, 1979), resilience and low cost (Chupas et al, 2008). This poly(oxydiphenylene-pyromellitimide) polyimide ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of PI photoconductivity has also been of great interest. Photogenerated intra- or intermolecular charge transfer by the absorption of radiation contributes to the photoconductivity of a polymer. Using Kapton PI, the chromophores responsible for photoconduction were identified as radical anions. , The photoconduction is believed to follow the hopping of charge between the adjacent pyromellitic imide (PMDI) units by the assistance of an electric field. The initial photophysical process of the interaction of PI with light was studied mainly by Freilich and Lee. , Freilich showed that the addition of a small number of electron donors to PI results in an increase in the photocurrent .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of PI photoconductivity has also been of great interest. [14][15][16][17][18][19][20] Photogenerated intra-or intermolecular charge transfer by the absorption of radiation contributes to the photoconductivity of a polymer. [21][22][23][24] Using Kapton PI, the chromophores responsible for photoconduction were identified as radical anions.…”
Section: Introductionmentioning
confidence: 99%
“…For ice, τ ranges from O(1 − 10 ns) and is strongly dependent upon the temperature of the ice [42]. For HDPE, the lifetimes are comparable to those of cold polar ice [43].…”
mentioning
confidence: 99%